Targeting Xcr1 on Dendritic Cells Rapidly Induce Th1-Associated Immune Responses That Contribute to Protection Against Influenza Infection - Tesfaye, Demo Yemane; Bobic, Sonja; Lysén, Anna; Huszthy, Peter Csaba; Gudjonsson, Arnar; Braathen, Ranveig; Bogen, Bjarne; Fossum, Even (Frontiers in Immunology, 2022)
Targeting antigen to conventional dendritic cells (cDCs) can improve antigen-specific immune responses, and additionally be used to influence the polarization of the immune responses. However, the mechanisms by which this is achieved are less clear. To improve our understanding, we here evaluate molecular and cellular requirements for CD4+ T cell and antibody polarization after immunization with Xcl1-fusion vaccines that specifically target cDC1s. Xcl1-fusion vaccines induced an IgG2a/IgG2b dominated antibody response, and rapid polarization of Th1 cells both in vitro and in vivo. For comparison, we included fliC-fusion vaccines that almost exclusively induced IgG1, despite inducing a more mixed polarization of T cells. Th1 polarization and IgG2a induction with Xcl1-fusion vaccines required IL-12 secretion, but was nevertheless maintained in BATF3-/- mice which lack IL-12 secreting migratory DCs. Interestingly, induction of IgG2a-dominated responses were highly dependent on the early kinetics of Th1 induction, and was important for optimal protection in an influenza infection model. Early Th1 induction was dominant, since a combined Xcl1- and fliC-fusion vaccine induced IgG2a/IgG2b polarized antibody responses similar to Xcl1-fusion vaccines alone. In summary, our results demonstrate that targeting antigen to Xcr1+ cDC1s is an efficient strategy for enhancing IgG2a antibody responses through rapid Th1 induction, which can be utilized for improved vaccine design.